Archaeological research of Southern Bessarabia in the Historical Society of Nestor the Сhronicler - O. O. Hrytsiuta (History of science and technology, 2017)
The article highlights the role of the Historical Society of Nestor the Chronicler in the development of archaeological research in South Bessarabia. The main direction of the work of the Society in this area was the study of burial mounds and their historical interpretation. A special role in these studies belongs to Professor F. I. Knauer. He for the first time in historical science conducted a large-scale and systematic archaeological and cartographic survey barrow`s groups of Akkerman district, and also made a description of burial mounds. F. I. Knauer, for the first time in historiography, the problem of ethnic identification of the ancient population of our region was formed.